Is Iron Status an Additional Barrier to Smoking Cessation in Females? An ERP Analysis. - Boozary, Laili K. (My University, 2022)
It has been well-established that females achieve lower cessation rates than males in traditional smoking cessation interventions. Research suggests that iron status variations (i.e. deficiency) are common in females. Iron status variations are known to alter dopamine (DA) pathways and learning ability involved in reward processing and addiction. This suggests a mediation model which may partially explain the sex differences in cessation rates wherein iron status predicts abstinence directly and indirectly via changes to reward processing. The current study enrolled 54 females at the onset of smoking cessation intervention and measured cognitive task behavior with concurrent electroencephalography (EEG). In addition, assays were run to extract iron biomarkers from a blood sample. ERP components known to be sensitive to reward learning were extracted from the EEG data. Task behavior was quantified in terms of accuracy and/or reaction time. Lastly, blink rates were extracted from the EEG to act as a proxy for dopaminergic status. After imputing missing data and using a Bayesian variable selection framework to select a final set of mediators, a Generalized Structured Component Analysis was employed to test three mediation models. Results revealed that iron status, task behavior, dopamine status, and neural components accounted for 1/3 of the variance in smoking cessation. These outcomes suggest that iron status may play a role in success or failure in achieving cessation during a quit attempt. These results may have implications for future smoking cessation intervention standards of care.
Keywords: Neuroscience of Addiction; Smoking Cessation; Health Disparities in Tobacco; Impacts of Iron Deficiency